On a convergence class for Dirichlet series - Mulyava, Oksana; Sheremeta, Miroslav (My University, 2000)
A relation between the maximum of the modulus, the maximal term and coefficients of Dirichlet series in terms of a convergence class is investigated. Досліджено зв’язок між максимумом модуля, максимальним членом і коефіцієнтами ряду Діріхле в термінах класів збіжності.
Keywords: maximal term; entire function; Dirichlet series; максимальний член; ціла функція; ряди Діріхле; кафедра вищої математики імені проф. Можара В. І.